Optimalisasi Pengembangan Sumber Daya Manusia melalui Pelatihan dalam Menjawab Tantangan Global - Silvi Lailatul Nur Janah; Chindy Padma Viradani; Faruq Ardiansyah (Yayasan Aya Sophia Indonesia, 2025)
Amidst increasingly fierce global competition, companies need to rely on high-quality employees who are flexible to changes in the fast-paced business world. One of the main approaches to achieving this is by implementing effective human resource training and development programs. This text explores the significance of such practices in facing global challenges, taking into account technological developments and ever-increasing market demand. We look at how training and development can improve employee skills, increase work efficiency, and reduce training and recruitment costs. With proper implementation, companies can improve the quality of their human resources, strengthen their competitive position, and solidify their existence in the global market. This text also reviews various methods and best practices in training and human resource development that support the achievement of company goals. In our view, this approach is not only reactive to change, but also proactive in building long-term resilience for the company.